My life next door - Fitzpatrick, Huntley (Dial Books, 2012)
When Samantha, the seventeen-year-old daugher of a wealthy, perfectionistic, Republican state senator, falls in love with the boy next door, whose family is large, boisterous, and just making ends meet, she discovers a different way to live, but when her mother is involved in a hit-and-run accident Sam must make some difficult choices.